Penggunaan Metode Pembelajaran Berbasis Game Based Learning dalam Meningkatkan Pemahaman Aqidah Akhlak Siswa Kelas III MI As’adiyah Bontang Tahun Pelajaran 2024/2025 - Sari, Eka Dara Jean Retno; Ihsan, Muh. (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to examine the use of the Game Based Learning (GBL) method in improving the understanding of faith and morals among third-grade students at MI As'adiyah Bontang. This study is expected to provide new insights into the development of more interactive and applicable learning methods to strengthen students' understanding of religion and morals. This study uses a qualitative approach to gain an in-depth understanding of the influence of GBL on students' understanding of faith and morals. In this study, data collection techniques include interviews, observation, and documents. Interviews were conducted with the principal, faith and morals teachers, and students to explore their views on game based learning. For data analysis, this study used thematic analysis, where data obtained from interviews and observations were analyzed by identifying the main themes related to GBL in improving students' understanding of aqidah akhlak. The results of this study are expected to provide new insights into the development of more interactive and applicable learning methods, as well as contribute to improving the quality of religious education in elementary schools. The conclusion shows that the application of game based learning can be a useful alternative in the learning process in elementary schools, especially in teaching aqidah and akhlak. With better support from facilities and resources, the application of GBL has great potential to improve the quality of learning and character of students in the future